De ratones y hombres. Maus, de Art Spiegelman - Faxedas Brujats, M. Lluïsa (Escritura e Imagen, 2010)
This article analyses the comic book Maus, by Art Spiegelman (1986-1991), as a work of art dealing with the Holocaust, and as a comic that subverts the fictional tradition of the genre, opening itself up to history and the narration of reality. Maus, the first comic book to treat the topic of the Holocaust in depth, was written by a second-generation witness. It is a story of both physical survival and enduring trauma in the family. At the same time, an analysis of the strategies by which Maus revises and subverts some of the most characteristic elements of the traditional comic reveals how Spiegelman has used the genre to recount, instead of fiction and for the first time, a historically authentic biographical tale.
Keywords: Cómic; Maus; Art Spiegelman; Holocaust